1974
DOI: 10.1111/j.1944-9720.1974.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of University Students About Language Teaching

Abstract: University language students, writing in the essay portion of a recent departmental opinion questionnaire, clearly indicate that they wish more speaking practice and less ritualized grammar in their language training. Rather than studying language as if it were a museum exhibit under glass, they prefer experiencing its live, practical aspects in such a way that they can gain mastery over a central core of high‐frequency usage for their daily use. They also want professors who are willing to teach living langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
9
0
3
Order By: Relevance
“…Despite the apparent changes in FL pedagogy during the past 3 decades, student views are strikingly similar to the concerns students expressed over 25 years ago in reports by Walker (1973), Normand (1973, and Schotta (1973). Although some students found their classroom experiences to be positive, especially when they reflected on their interactions with teachers, overall, students were critical of the types of activities they encountered in their FL study.…”
Section: Affect and Preferences In Fl Classroomssupporting
confidence: 60%
See 1 more Smart Citation
“…Despite the apparent changes in FL pedagogy during the past 3 decades, student views are strikingly similar to the concerns students expressed over 25 years ago in reports by Walker (1973), Normand (1973, and Schotta (1973). Although some students found their classroom experiences to be positive, especially when they reflected on their interactions with teachers, overall, students were critical of the types of activities they encountered in their FL study.…”
Section: Affect and Preferences In Fl Classroomssupporting
confidence: 60%
“…Walker (1973) found calls for change by university FL students in his analysis of approximately 1,200 questionnaires. Students expressed a need for more "opportunity to use, under controlled conditions, what they are learning" (p. 102), less grammar instruction, and less error correction.…”
Section: Studies On Attitudes Toward Fl Instructionmentioning
confidence: 96%
“…The purpose of the present study, therefore, is to catalogue and report the perceptions and attitudes of recent incoming college students (freshman and transfer students) concerning L2 study-a snapshot of current student beliefs. General student attitudes and opinions have shifted from a negative position in the early 1970s (Schotta, 1973;Walker, 1973), to one of tremendous support (ACE, 2000; Art and Science Group, 2001;Roberts, 1992), with a host and range of arguments given in substantiation. This study, however, examines the position of incoming college freshmen in a post-9/11, mid-War-on-Terror America.…”
Section: Present Studymentioning
confidence: 99%
“…Walker (1973) analyzed 1,200 questionnaires completed by university students wherein the majority of respondents felt that the foreign language requirement should be abolished. Also targeting university students in the same year, the 265 respondents to Schotta' s 1973 questionnaire overwhelmingly shared a desire to eliminate the foreign language requirement.…”
Section: Introductionmentioning
confidence: 99%
“…While learners' developing proficiency levels across the three communicative modes (interpersonal, interpretive, and presentational) are undoubtedly intertwined to varying degrees, second language (L2) learners are often particularly focused on acquiring a high level of speaking proficiency (Harlow & Muyskens, ; Walker, ). Rivera and Matsuzawa () found that speaking was the number one foreign language learning goal identified by the 48 learners whom they surveyed, including students of both commonly taught and some less commonly taught languages.…”
Section: Introductionmentioning
confidence: 99%